Attributes Contributing Core Competencies: A Study of KVK Personnel in Bihar and Jharkhand States - Sinha, S.K.; Gupta, Sanjay Kumar; Nain, M.S.; Kumar, G.A.K. (Indian Journal of Extension Education, 2021)
The KVKs provide multidisciplinary and broad based technological interventions to enable farmers manage their farm in a sustainable and integrated manner. This demands enhanced manpower not only in terms of number but also covering the most important subject matter areas relevant to the district. Personal, communication, motivational and leadership skills are considered important for problem solving and attaining the objective of any organization. This study considered 123 personnel working under the jurisdiction of ATARI, Patna. Semi structured questionnaire (using Google form) seeking qualitative and quantitative data was used as measurement tool. It was found that the respondents were working under the Administrative control of ICAR, SAU of the zone, NGOs and State Government. Majority of the respondents perceived themselves having good to very good personal skills, communication skills and the skills to identify and solve field level problem. The administrative control of KVK, area of specialization and academic qualification were positively significantly correlated with level of knowledge, whereas designation, age, gender and marital status were positively non-significantly correlated, but distance was negatively non-significantly correlated with the level of knowledge. The leadership qualities were significantly positively correlated with distance, administrative control of KVKs, academic qualification, area of specialization, whereas designation, age, gender and marital status were negatively non-significantly correlated. The multiple regression analysis showed that four variables namely administrative control, academic qualification, area of specialization and experience contributed significantly to level of knowledge. The leadership qualities contributed significantly by administrative control, academic qualification and area of specialization.
Keywords: Core competencies; KVK; Personal skills; Leadership qualities; Knowledge Level; Communication skills; Problem identification; Problem solving; Skills